2014
DOI: 10.4209/aaqr.2013.03.0100
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Properties of Macromolecular Carbon on de Novo Synthesis of PCDDs, PCDFs, PCBs, and Chlorobenzenes

Abstract: We examined the influence of the properties of macromolecular carbon on thermochemical de novo synthesis of toxic chlorinated aromatic compounds (aromatic-Cls), such as polychlorinated dibenzo-p-dioxins (PCDDs), furans (PCDFs), biphenyls (PCBs), and chlorobenzenes (CBzs). Six types of macromolecular carbons were prepared. Some activated carbon samples were modified by chemical solvents, such as nitric acid, hydrogen peroxide, sulfuric acid, and urea solutions, to change the properties of the activated carbon. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…The band located at 1570 cm -1 is assigned to the stretching of the C=C bond due to incomplete polymerization. Fujimori et al (2014) reported a similar conclusion in their study. In the lower region of the spectra, the band around 1050 cm -1 could be due to antisymmetric stretching vibrations of the C-O-C group or also to out-of-plane C-H bending.…”
Section: Ftir Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…The band located at 1570 cm -1 is assigned to the stretching of the C=C bond due to incomplete polymerization. Fujimori et al (2014) reported a similar conclusion in their study. In the lower region of the spectra, the band around 1050 cm -1 could be due to antisymmetric stretching vibrations of the C-O-C group or also to out-of-plane C-H bending.…”
Section: Ftir Analysissupporting
confidence: 80%
“…In their study, the ammonia treatment of activated carbon resulted in lower BET surface areas compared with the parent material. Also, Cansado et al (2012) and Fujimori et al (2014) found that these modifications usually decreased the surface area of activated carbon due to the shrinkage and blockage of the micropores. The modification procedures could damage the highly ordered structures and cause the ordered structures to collapse.…”
Section: Temmentioning
confidence: 99%
“…Combustion processes (Correa et al, 2006;Shih et al, 2006;Chiu et al, 2011) involving chlorine containing organic matter ) such as municipal solid waste incineration (Lee et al, 2003), laboratory waste incinerators (Liao et al, 2014;Wu et al, 2014), hazardous waste incinerators , iron ore sintering plants (Fang et al, 2011), steel and cement kilns (Van Thuong et al, 2014), landfill fires (Moussiopoulos et al, 2006), vehicle tailpipe exhausts (Chuang et al, 2010), boilers , fast food restaurants , coal fire-power plants (Lin et al, 2010b), bio-mass open burning (Shih et al, 2008;Chang et al, 2013;Chang et al, 2014) and dust storms (Chi et al, 2014) have been pointed out to be among the leading primary sources of PCDD/Fs and other dioxin like compounds. The emission of PCDD/Fs from the mentioned processes can be attributed to either their presence the feedstock, or be formed from chlorine containing precursors compounds as well as be formed through the de novo mechanism at certain temperature window Fujimori et al, 2014). PCDD/Fs are also classified as semi-volatile organic compounds (SVOCs) and when they are released into the atmosphere, they are ultimately subjected to atmospheric dispersion and deposition processes (Halsall et al, 1997;Shih et al, 2006) to the environmental compartments or sinks such as water bodies, soil and vegetation (Halsall et al, 1997;Ren et al, 2007).…”
Section: Introductionmentioning
confidence: 99%